Technology Entrepreneurial Ecosystems and Entrepreneurship in the West Region of Romania - Roja, Alexandru (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Technical progress and entrepreneurship have become drivers of economic and social stability and progress. To develop their new ventures, to generate value, and to validate and implement business ideas, entrepreneurs need a competitive business environment, we name it technology entrepreneurial ecosystem. Entrepreneurial new ventures competitiveness depends on the entrepreneurial ecosystem structure and components. Our research presents the main levels of information technology industry linked with technology entrepreneurial ecosystems components. In the second part of our research we present the entrepreneurs perception about information technology entrepreneurial ecosystem in the west region of Romania. Our objective was to find out the entrepreneurs point of view about opportunities and influences that they perceive in the regional entrepreneurial ecosystem.